ENTREPRENEURSHIP IN AFRICA: SOCIAL WORK CHALLENGES FOR HUMAN, SOCIAL AND ECONOMIC DEVELOPMENT1 - Lombard, Antoinette (Social Work/Maatskaplike Werk, 2003)
In Africa a new understanding and thinking of entrepreneurship needs to be contextualised as part of the challenge to alleviate poverty. This challenge was confirmed when most of the heads of state committed themselves to addressing poverty as the top priority for their countries’ agendas when they signed the Declaration at the World Summit on Social Development (1995) and adopted Agenda 21, the agenda for sustainable development in the 21st century, during the United Nations Conference on Environment and Development (Rio de Janeiro, 1992). Whilst there is consensus amongst world leaders that they want to reduce global poverty by half by 2015, the policies and strategies to achieve this were still being negotiated during the follow up to the World Summit for Sustainable Development in South Africa in August/September, 2002.